STRATEGI MEDIA SOSIAL BERBANTUAN INSTAGRAM DALAM MENINGKATKAN BRANDING IMAGE LEMBAGA PENDIDIKAN ISLAM - Lizamatun Nafilah; Eka Diana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital era has brought significant changes in various sectors, including education. Social media, especially Instagram, has an important role in building the brand image of Islamic educational institutions. This study aims to analyse Instagram-assisted social media strategies in improving the brand image of Islamic educational institutions and identify the supporting and inhibiting factors. The method used is a qualitative approach with a case study at MA Nurul Jadid, Paiton, Probolinggo. Data were obtained through observation, in-depth interviews with the principal and social media manager, and documentation of Instagram uploads. The results showed that effective utilisation of Instagram can strengthen the brand image of Islamic educational institutions through visual communication strategies, interaction with the community, and storytelling-based content. However, challenges such as lack of professional staff, lack of consistent content strategy, and lack of understanding of community preferences are still the main obstacles. Therefore, a more structured and Islamic values-based social media management is needed to increase the attractiveness and trust of Islamic educational institutions.